2014
DOI: 10.1186/1471-2164-15-1136
|View full text |Cite
|
Sign up to set email alerts
|

Swimming-induced exercise promotes hypertrophy and vascularization of fast skeletal muscle fibres and activation of myogenic and angiogenic transcriptional programs in adult zebrafish

Abstract: BackgroundThe adult skeletal muscle is a plastic tissue with a remarkable ability to adapt to different levels of activity by altering its excitability, its contractile and metabolic phenotype and its mass. We previously reported on the potential of adult zebrafish as a tractable experimental model for exercise physiology, established its optimal swimming speed and showed that swimming-induced contractile activity potentiated somatic growth. Given that the underlying exercise-induced transcriptional mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 79 publications
5
59
0
1
Order By: Relevance
“…Evident increases in the muscle mass and body weight of rats from Groups VI, VII, VIII, and IX as compared to that of the exercised control group confirmed the myostatin inhibitory role of both MIMBP and PMIMBP supplements suggesting their protective influence against muscle wasting conditions. Exercise induces alterations in muscle fiber morphometry and capillarization in tissues 65 . There is a need for detailed morphometrical assessment of the exercised gastrocnemius muscles to trace and quantitate the effects of MIMBP and PMIMBP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Evident increases in the muscle mass and body weight of rats from Groups VI, VII, VIII, and IX as compared to that of the exercised control group confirmed the myostatin inhibitory role of both MIMBP and PMIMBP supplements suggesting their protective influence against muscle wasting conditions. Exercise induces alterations in muscle fiber morphometry and capillarization in tissues 65 . There is a need for detailed morphometrical assessment of the exercised gastrocnemius muscles to trace and quantitate the effects of MIMBP and PMIMBP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we find that gene expression, which is demonstrably both heritable and plastic, is likely an important mechanism for the replicated and parallel phenotypic diversification of Arctic charr ecotypes, contributing to differences and similarities, even across divergent evolutionary lineages. We find sets of genes that are biologically relevant based on human and model organism studies (Morbey et al 2010;Palstra et al 2014;Flanagan et al 2017;Ronkainen et al 2008) and are associated with traits that differ between these and other fish ecotype divergences, such as haemoglobins (Supplementary figure S9c) (Evans et al 2012;Filteau et al 2013). This is consistent with the transcriptome being a flexible and rapid response to selection (Schneider & Meyer 2017) that can facilitate convergent evolution across ecotypes and species (e.g.…”
Section: Variable and Non-parallel Evolutionary Histories Underlie Pamentioning
confidence: 92%
“…6c). These genes are known to be associated with growth rate, body size, and metabolism (Morbey et al 2010;Palstra et al 2014;Flanagan et al 2017), making them strong candidates for underlying ecotype divergence in Arctic charr. Additionally, 19 differentially expressed genes were shared across four ecotype pairs, which included several haemoglobin subunits ( Supplementary Fig.…”
Section: Variable and Non-parallel Evolutionary Histories Underlie Pamentioning
confidence: 99%
“…34) Apoptotic cell death and muscle growth are normal parts of myogenesis following exercise. 35) Palstra et al 36) showed that the expression of GAPDH and other myogenesis-related genes were increased in white muscle upon exercise in zebrafish. Thus, we assume that the high expression of these glycolytic genes in the white muscle of tuna is related to their highly muscled body.…”
Section: Multifunction Of the Highly Expressed Glycolytic Genesmentioning
confidence: 99%